An analytical perspective of Afrikaner ideological hegemony (1961-1980): the role of politics and rugby - Labuschagne, P. A. H. (Faculty of the Humanities, University of the Free State, 2015)
Afrikaner ideological hegemony was well established in the decade 1961-1970, both on the political terrain and on the rugby field. In both instances, Afrikaner political prowess and masculinity were dominant and Afrikaner ideological hegemony firmly established. On the political front, internal black resistance was successfully suppressed and the white parliamentary opposition fragmented and ineffective. The attainment of independence from the Commonwealth and the declaration of South Africa as a Republic in 1961 were supported by a sharp upswing on the economic front, which also coincided with major triumphs on the rugby field by the Springboks. However, the international scene was changing and the racist sports policies, enforced by the National Party government, translated into the All Blacks’ refusal to tour South Africa. Prime Minister John Vorster made superficial changes to dismantle “petty” apartheid, which made it possible for the All Blacks to include Maori players in their team. On the political front, however, developments took place that soon eroded the monolithic Afrikaner ideological hegemony. The right-wingers split from the National Party to form the “Herstigte Nasionale Party” (or translated, the Reformed National Party). Although the break was insignificant at first, the cracks in the solidarity of the National Party soon widened. In the next decade (1971-1980) there was an upsurge in black resistance and, as opposed to previous decades, it was better organised and with much more force. This time the resistance was able to seriously threaten the apartheid regime’s resolve and confidence. On the rugby field, the situation was not much better. The Springboks was beaten in 1972 by an average English team and humiliated by the British Lions in 1974 when they were unable to win a single test on home soil. The decade 1971-1980 therefore formed a sharp contrast and stood in contradiction to the previous decade when Afrikaner ideological hegemony was at its peak. In contrast, the 1971-1980 decade was a period of decline and a period when the Afrikaner largely lost its dominance and its monolithic character. The National Party had to move to the left of the Conservative Party and this started a process to normalise sport in the country
Keywords: Afrikaner; Ideological hegemony; Springboks; Rugby; British Lions; National Party